THE IMPACT OF BUREAUCRATIC REFORM ON INDONESIAN GOVERNANCE: A PERSPECTIVE REVIEW OF ACADEMIC LITERATURE - Hidayat, Fauzan (Fakultas Politik Pemerintahan, 2023)
This scientific journal examines the impact of bureaucratic reform on governance in Indonesia from an academic literature perspective. Indonesia, as a country with high administrative complexity, has undergone significant changes in its government system since the era of reform in the late 1990s. Before the reform, issues of inefficiency, overlapping authorities, and slow bureaucracy were major concerns in the public sector. This study aims to analyze the concrete impact of bureaucratic reform efforts, identify changes in governance, and provide a comprehensive overview of these changes. The literature review method is used to absorb the development of concepts, theories, and empirical findings that already exist. This article also reviews the history of bureaucratic reform, key elements in the reform, its impact on efficiency, accountability, public service, and community participation, as well as the challenges and obstacles in its implementation.